Status of Indigenous Languages within Gambian Education Policy: English vs Vernacular Languages as the vehicular language in formal education contexts - Biel, Leyre Alejaldre (2014)
Taking into consideration the National Education Policy (2004-15) that encourages the respect and preservation of indigenous languages of The Gambia and emphasizes the need to use vernacular languages during the first stages of formal education, this paper presents the results from observing the languages used to teach within the Gambian classrooms. The investigation in the field focuses on finding and understanding the reasons that lead educators to choose either the vernacular language or the colonial language. The fieldwork is mainly conducted in lower basic schools in The Gambia, because it is the critical period when learners develop languages skills and will impact on the future acquirement of other foreign languages. Furthermore, the paper presents and explains briefly the situation within the whole education system from lower basic to tertiary education.